Suppression of Rheumatoid Arthritis B Cells by XmAb5871, an Anti‐CD19 Antibody That Coengages B Cell Antigen Receptor Complex and Fcγ Receptor IIb Inhibitory Receptor. Issue 5 (May 2014) - Chu, Seung Y.; Yeter, Karen; Kotha, Roshan; Pong, Erik; Miranda, Yvonne; Phung, Sheryl; Chen, Hsing; Lee, Sung‐Hyung; Leung, Irene; Bonzon, Christine; Desjarlais, John R.; Stohl, William; et al.
<x xml:space="preserve">Abstract</x> Objective Engagement of Fcγ receptor IIb (FcγRIIb) suppresses B cell activation and represents a promising target for therapy in autoimmunity. The aim of this study was to characterize B cell immunosuppression mediated by the Fc‐engineered antibody, XmAb5871, which coengages FcγRIIb with the B cell antigen receptor (BCR) complex and that is currently in clinical development for the treatment of rheumatoid arthritis (RA). Because rheumatoid factor (RF) might interfere with the binding of XmAb5871 to FcγRIIb, we correlated RF titers with the potency of XmAb5871. Methods We analyzed the expression of CD19, FcγRIIb, and CD86 on naive and memory B cells from 50 patients with RA and 66 healthy donors, quantified XmAb5871‐induced promotion of FcγRIIb phosphorylation and suppression of calcium flux in activated B cells, measured CD86 inhibition in whole blood, and correlated RF and anti−citrullinated protein antibody (ACPA) levels with drug potency. We engrafted RA peripheral blood mononuclear cells (PBMCs) into SCID mice, treated them with XmAb5871, and quantified human total IgG, total IgM, and anti‐tetanus IgG antibody levels in vivo. Results B cells from all donors expressed CD19 and FcγRIIb, and the expression of FcγRIIb was higher on naive, but not memory, B cells from donors with RA compared with healthy donors. BCR‐mediated calcium flux was suppressed by XmAb5871 and was associated with FcγRIIb phosphorylation. XmAb5871 inhibited CD86 induction, and the levels of RF and ACPAs did not affect efficacy. XmAb5871 suppressed B cell activation regardless of disease severity. In SCID mice engrafted with PBMCs from a patient with RA, XmAb5871 suppressed humoral responses. Conclusion Coengagement of the BCR complex and FcγRIIb by XmAb5871 inhibits B cell activation and function. The similar potency in patients with RA and healthy donors and the absence of autoantibody interference suggest that XmAb5871 may represent a new therapeutic strategy to suppress autoreactive B cells in RA.